Free Lateral Great Toe Flap for the Reconstruction of Finger Pulp Defects - Zheng, Huaiyuan; Liu, Juan; Dai, Xinyi; Machens, Hans-Günther; Schilling, Arndt F. (Journal of Reconstructive Microsurgery, 2015)
Introduction The aim of this study was to evaluate the esthetic and sensory outcomes after reconstruction of finger pulp defects with free toe flaps from the lateral aspect of the great toe.Methods From June 2006 to October 2011, we performed 48 free toe pulp transfers for finger pulp reconstruction in 43 patients; 18 male and 25 female patients with a mean age of 31.8 years (range, 16–47 years). Six patients suffered multiple digital pulp defects and five received two synchronous pulp transfers. The defects involved 20 thumbs, 15 index fingers, 10 long fingers, and 4 ring fingers, and flap size ranged from 24 × 18 to 55 × 30 mm. Follow-up evaluation included the functional and esthetic outcomes of the reconstructed pulps and donor toes.Results All but one flap survived completely. Overall, 32 cases (35 pulp flaps) were followed for more than 1 year (range, 12–48 months; average, 22.8 months). The Semmes–Weinstein sensitivity score was 2.83 to 4.74 at the flaps and the mean static two-point discrimination was 6.17 mm (range, 3–10 mm). A total of 13 patients (40.6%) experienced mild (10 cases) to moderate (3 cases) cold intolerance, and 1 patient (3.1%) suffered severe cold intolerance. According to the Michigan Hand Outcome Questionnaire the mean esthetic appearance score was 16 (range, 12–19).Conclusion The free neurovascular great toe pulp flap is an efficient and reliable flap for the reconstruction of finger pulp defects.
Keywords: free pulp flap; finger pulp defect; great toe